2013
DOI: 10.1037/a0026311
|View full text |Cite
|
Sign up to set email alerts
|

Reversal learning in rats (Rattus norvegicus) and pigeons (Columba livia): Qualitative differences in behavioral flexibility.

Abstract: Research has shown that pigeons given a simultaneous visually based discrimination reversal, in which a single reversal occurs at the midpoint of each session, consistently show anticipation prior to the reversal as well as perseveration after the reversal, suggesting that they use a less effective cue (time or trial number into the session) than what would be optimal to maximize reinforcement (local feedback from the most recent trials). In the present research, pigeons (Columba livia) and rats (Rattus norveg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 38 publications
7
91
3
1
Order By: Relevance
“…Mackintosh, Brendan, & Valerie, 1968;Mackintosh & Little, 1969) or to local feedback (e.g. Rayburn-Reeves, Stagner, Kirk, & Zentall, 2013) is an important factor in completing the reversal learning task more efficiently. Appropriately directed attention allows animals to achieve efficiency by making associations between the relevant cues and the rewards, but this is more likely to happen if the experimental design is ecologically relevant to the study species.…”
Section: Introductionmentioning
confidence: 99%
“…Mackintosh, Brendan, & Valerie, 1968;Mackintosh & Little, 1969) or to local feedback (e.g. Rayburn-Reeves, Stagner, Kirk, & Zentall, 2013) is an important factor in completing the reversal learning task more efficiently. Appropriately directed attention allows animals to achieve efficiency by making associations between the relevant cues and the rewards, but this is more likely to happen if the experimental design is ecologically relevant to the study species.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the current experiments, rats and pigeons were not much different from one another in the Switch group. Rats have been proposed to be much faster to learn to switch than pigeons (Rayburn-Reeves et al, 2013), so it was thought that perhaps rats would perform better than pigeons on the MHD task. This hypothesis was not supported by the current results.…”
Section: Discussionmentioning
confidence: 99%
“…However, nonhuman subjects provide a way to test different aspects of the MHD free of these influences. Recently, evidence has been found that rats show more behavioral flexibility and will alternate and switch choices more readily than pigeons (Rayburn-Reeves et al, 2013). This result was found after giving rats experience with a spatial midsession reversal-learning task.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thomas Zentall and his colleagues have investigated a striking example of inefficient choice behavior in nonhuman animals (e.g., Laude, Stagner, Rayburn-Reeves, & Zentall, 2014;Rayburn-Reeves, Molet, & Zentall, 2011;Rayburn-Reeves, Stagner, Kirk, & Zentall, 2013;Stagner, Michler, Rayburn-Reeves, Laude, & Zentall, 2013; see also Cook & Rosen, 2010;Daniel, Cook, & Katz, 2015;McMillan & Roberts, 2015;McMillan, Sturdy, & Spetch, 2015). An early article in this experimental series presents several experiments that are illustrative of the basic effect.…”
Section: Behavioral Variabilitymentioning
confidence: 99%